Validation of the IMPEDE VTE score for prediction of venous thromboembolism in multiple myeloma: a retrospective cohort study. (17th May 2021) - Covut, Fahrettin; Ahmed, Ramsha; Chawla, Sanchit; Ricaurte, Frank; Samaras, Christy J.; Anwer, Faiz; Garcia, Alex V. M.; Angelini, Dana E.; Mazzoni, Sandra; Faiman, Beth; Valent, Jason; Khouri, Jack
Summary: The IMPEDE VTE score has recently emerged as a novel risk prediction tool for venous thromboembolism (VTE) in multiple myeloma (MM). We retrospectively reviewed 839 patients with newly diagnosed MM between 2010 and 2015 at Cleveland Clinic and included 575 patients in final analysis to validate this score. The c‐statistic of the IMPEDE VTE score to predict VTE within 6 months of treatment start was 0·68 (95% CI: 0·61–0·75). The 6‐month cumulative incidence of VTE was 5·0% (95% CI: 2·1–7·9) in the low risk group, compared to 12·6% (95% CI: 8·9–16·4%) and 24·1% (95% CI: 12·2–36·1) in the intermediate and high risk groups ( P  < 0·001 for both). In addition, a higher proportion of patients in the VTE cohort had ECOG performance status of ≥2 as compared to the no VTE cohort (33% vs. 16%, P  = 0·001). Other MM characteristics such as stage, immunoglobulin subtype, and cytogenetics were not predictors of VTE. In summary, we have validated the IMPEDE VTE score in our patient cohort and our findings suggest that it can be utilized as a VTE risk stratification tool in prospective studies looking into investigating VTE prophylaxis strategies in MM patients.